2023
DOI: 10.3390/cryst13010109
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, Shape Memory Effect, Chemical Composition and Corrosion Resistance Performance of Biodegradable FeMnSi-Al Alloy

Abstract: The medical applications of degradable iron-based biomaterials have been targeted by re-searchers due to their special properties that they present after alloying with various elements and different technological methods of obtaining. Compared to other biodegradable materials, iron-based alloys are designed especially for the low production costs, the non-magnetism obtained by alloying with Mn, and the shape memory effect (SME) following the alloying with Si, which is necessary in medical applications for whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…To make the samples more electrically conductive, a Luxor Au SEM COATER—CT-2201-0144 (Kusterdingen, Germany) was used to deposit a 5 nm coating of gold to the surface and cross-section of the samples. An SEM FEI Quanta 200 3D microscope (Brno, Czech Republic) with the following specifications was used: Low vacuum mode, LFD (large field detector), HV (high voltage): 20 kV, WD (working distance): 10 mm, comparable to previous research [ 28 ], and a Vega TESCAN LMHII SEM microscope (Brno, Czech Republic) with the following parameters [ 29 ]: secondary electrons (SE) detector, electron gun supply: 30 kV, high vacuum, and 15.5 mm working distance. X-ray diffractions were performed using a Panalytical Xpert PRO MPD 3060 (Almelo, The Netherlands) facility equipped with a Cu X-ray tube (K = 1.54051), 2Theta: 20°–90°, step size: 0.13°, time/step: 51 s, and a scan speed of 0.065651°/s in the reflection mode.…”
Section: Methodsmentioning
confidence: 99%
“…To make the samples more electrically conductive, a Luxor Au SEM COATER—CT-2201-0144 (Kusterdingen, Germany) was used to deposit a 5 nm coating of gold to the surface and cross-section of the samples. An SEM FEI Quanta 200 3D microscope (Brno, Czech Republic) with the following specifications was used: Low vacuum mode, LFD (large field detector), HV (high voltage): 20 kV, WD (working distance): 10 mm, comparable to previous research [ 28 ], and a Vega TESCAN LMHII SEM microscope (Brno, Czech Republic) with the following parameters [ 29 ]: secondary electrons (SE) detector, electron gun supply: 30 kV, high vacuum, and 15.5 mm working distance. X-ray diffractions were performed using a Panalytical Xpert PRO MPD 3060 (Almelo, The Netherlands) facility equipped with a Cu X-ray tube (K = 1.54051), 2Theta: 20°–90°, step size: 0.13°, time/step: 51 s, and a scan speed of 0.065651°/s in the reflection mode.…”
Section: Methodsmentioning
confidence: 99%
“…It was observed that the main corrosion products passed from the surface into the solution during the immersion and cleaning steps. As the surface was covered with ZnO, which was the main corrosion product, a protective layer was formed at the beginning [74]. The zincite layer was repeatedly formed, and was penetrated by various ions in the electrolyte solution.…”
Section: Immersion Testsmentioning
confidence: 99%
“…This alloy belongs to the biodegradable materials class and can be functionalized considering SME for specific medical applications. Each of these classes of biodegradable alloys has advantages and disadvantages in terms of DR, mechanical properties and SME [ 5 ]. Mg-based alloys show both biocompatibility and good mechanical properties [ 6 , 7 , 8 , 9 , 10 , 11 ], but the DR is very high and hydrogen gas evolution has been observed in degradation [ 12 ].…”
Section: Introductionmentioning
confidence: 99%